Eventos climáticos e suas consequências em Franca - SP - Megda, Otávio Reis [UNESP] (2014)
Since the early twentieth century, urban expansion in Brazil has intensified with the given industrial migration, characterizing the process of urbanization. With this process (progress), some problems became evident sprawl and intensified by urban dynamics, in the last six years, the cost of investments to combat flooding in Franca - SP exceeded R$17 million, highlighting the problem of disposing in the city and the lack of effective solutions in the industry. In this paper, we propose a behavior analysis of climatic factors in the city of Franca, a discussion highlighting the rainfall and how urban behaves before the runoff. This council is an example of mid-sized cities industrialized and propensity to become great potential for urbanization, highlighting midiaticatly mainly flood and storm water impacts arising in the urban area. The objective is to make a proposal to check the body behaves as an urban locality (Franca - SP) compared to the rainfall during the rainy season and the impacts in this city